2013
DOI: 10.1155/2013/840295
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Ecological Impact of Human Settlement on the Water Quality of Lower Cross River, Nigeria

Abstract: The ecological impact of human settlement on the water quality of Lower Cross River, Nigeria was evaluated. The physical and chemical conditions of the river water were determined from January to August, 2011. Three stations comprising Itu in Akwa Ibom State with intense human activities (station 2), its upstream (without human settlement) at Cross River State (station 1) and the downstream (station 3) were sampled. The Parametric One Way Analysis of Variance (ANOVA) indicated that of the 17 physical and chemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 5 publications
0
1
1
Order By: Relevance
“…However, the result is not in line with Oribhabor et al (2013) that reported that DO level was lower than in the rainy season in the Lower Cross River, Nigeria. The higher DO values recorded in the Akor River between March and June may be attributed to early rainfall that has led to the increase in water volume, turbulence and increased dissolution of oxygen at air-water interface.…”
Section: Physical-chemical Parameterscontrasting
confidence: 95%
“…However, the result is not in line with Oribhabor et al (2013) that reported that DO level was lower than in the rainy season in the Lower Cross River, Nigeria. The higher DO values recorded in the Akor River between March and June may be attributed to early rainfall that has led to the increase in water volume, turbulence and increased dissolution of oxygen at air-water interface.…”
Section: Physical-chemical Parameterscontrasting
confidence: 95%
“…Humans have become an integral element of the ecology of the Cross River estuary due to its frequent closeness to population centers, biological diversity, high fisheries productivity, and recreational value (Oribhabor et al 2013). Indiscriminate mangrove harvesting, garbage disposal, multi-faceted pollution, and unsustainable fishing practices are all human-caused factors degrading the estuary's ecosystem.…”
Section: Introductionmentioning
confidence: 99%